Effect of packing materials and storage of scions on graft success in nutmeg (Myristica fragrans Houtt.) - KRISHNAMOORTHY, J REMA, B (Journal of Spices and Aromatic Crops, 1998)
Evaluation of various packing materials and storage of nutmeg (Myristica fragrans) scions indicated that storage of scions in sealed polythene bags and in moist coir dustin sealed polythene bags were the best and 63.7% and 62.2% graft success respectively, was obtained up to 10 days of storage.